1981
DOI: 10.1080/00039896.1981.10667635
|View full text |Cite
|
Sign up to set email alerts
|

Volcanoes and Carcinoma of the Thyroid: A Possible Association

Abstract: Environmental factors contributing to incidences of thyroid carcinoma are re-evaluated and emphasized in this study. Thyroid cancers appear to occur independent of endemic goiter, based on epidemiologic and histologic evidence. While environmental factors appear to be important, the specific etiologic agent has not yet been identified or suggested. The number of thyroid cancer incidences available from cancer registries are analyzed in an attempt to identify a specific environmental carcinogenic agent. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 4 publications
1
18
0
1
Order By: Relevance
“…Symptoms associated with hazmat exposures are often subtle or nonspecific and may have a latency effect (French and Holt, 1989). Longterm health effects associated with disaster-related hazardous material releases have been hypothesized but are particularly difficult to identify and confirm (Kung et al, 1981;Ziegler, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms associated with hazmat exposures are often subtle or nonspecific and may have a latency effect (French and Holt, 1989). Longterm health effects associated with disaster-related hazardous material releases have been hypothesized but are particularly difficult to identify and confirm (Kung et al, 1981;Ziegler, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…26 The authors of this hypothesis note that similar volcanos exist in the Philippines, and also may affect risk of thyroid cancer. Recently, high rates of thyroid cancer have been reported in other Pacific island populations, but the reasons for this remain unclear.…”
Section: Whites (For Women) or Intermediate Between Us-bornmentioning
confidence: 99%
“…While Iceland and Hawaii have 'basaltic low-viscosity' volcanoes with productive lava flows, the other areas have the 'Strombolian' type of eruptions that are highly viscous and produce minimal flows. He also emphasized the interest of possible differences (Favalli et al 2004) if the composition of the soil, which ultimately develops from these flows, was found to differ from the soils in other regions of the world (Kung et al 1981). Goodman et al (1988) reported thyroid cancer incidence in Hawaii, showing a significant variation on the basis of ethnicity, with the highest rates occurring in Filipino women (18.2/100 000) and Chinese men (6.3/100 000).…”
Section: Volcanic Areasmentioning
confidence: 99%
“…In 1970, a 5-year study revealed the incidence of thyroid cancer in Oahu, Hawaii, to be the highest in the world in women and among the highest in men (Haber & Lipkovic 1970). Kung et al (1981) reported that the presence of active volcanoes which produce abundant lava was the common denominator of Iceland and Hawaii, where the incidence of thyroid cancer is outstandingly high. He postulated the presence of a carcinogenic agent in the lava and also that the unexceptional incidences of thyroid cancer found in the volcanic areas of British Columbia, Japan, Cali, and Colombia were caused by differences in the type of underlying volcanoes.…”
Section: Volcanic Areasmentioning
confidence: 99%